Effects of sports initiation on the motor and psychic development of children in various age groups: A review systematic (Research, Society and Development, 2021)
Introduction: In addition to promoting healthy habits, sports initiation is important for the formation and development of the child's psychic and motor performance abilities. Objective: to verify the level of motor and mental development of children of different age groups participating in sports initiation programs. Methods: This study is a systematic review, searches were performed in the following databases: Science Direct, Pubmed, BVS, using the descriptors: motor development; psychic development; kids; sports initiation. The search in the database took place between January and May 2021. Results: A total of 196 articles were found on the topic discussed, in Portuguese, Spanish and English. After applying the criteria established for the research and reading of the articles, only 05 were selected for being in accordance with the research objective. Significant differences were obtained in studies that performed the correlation between motor development and participation in sports initiation programs. Conclusion: Sport initiation seems to play an important role in the motor and psychophysical development of children in various age groups.